Sublime Simplicity : An Alternative Approach to the Adaptive Reuse of a Quarry in Midrand, through Minimal Landscape Design - Shand, Dayle Lesley (University of Pretoria, 2019)
Mini Dissertation (ML (Prof))--University of Pretoria, 2019.